The association of remnant cholesterol (RC) and interaction between RC and diabetes on the subsequent risk of hypertension - Wang, Jie; Sun, Qi; An, Yu; Liu, Jia; Leng, Song; Wang, Guang (Frontiers in Endocrinology, 2022)
Purpose: Whether elevated remnant cholesterol (RC) is associated with hypertension (HTN), and whether elevated RC interacts with diabetes on the subsequent risk of HTN have not been illustrated. Thus, this study is aimed to investigate the associations and interactions of RC, diabetes, and the management of cardiovascular risk factors with the risk of incident HTN in a Chinese population. Patients and methods: This cohort study recruited 42,994 participants from April 2016 to August 2020 and follow-up from April 2017 to August 2021 in Dalian of China. RC was divided into quintiles as follows: the < 20% group, the 20–39% group, the 40–59% group, the 60–79% group, and the ≥ 80% group. This study finally included 17,006 participants who were free from HTN at baseline. Results: This study had 1861 (10.90%) HTN occurred, 205 (5.30%) in the first quintile of RC, 335(8.98%) in the second quintile of RC, 388(11.17%) in the third quintile of RC, 420(13.42%) in the fourth quintile of RC and 513(17.91%) in the fifth quintile of RC. Compared with participants in the first quintile of RC, participants in the fifth quintile of RC showed a greater risk of HTN events among participants with diabetes (hazard ratio (HR) 4.95, 95%confidence interval (CI) 1.05-23.39, P=0.0432) than among participants without diabetes (HR 1.67, 95% CI 1.26-2.22, P=0.0004, P for interaction =0.0420). Compared with participants without diabetes, participants with diabetes who have the ideal management of RC and other risk factors showed no excess risk of HTN. Conclusions: Elevated RC is significantly predictive of HTN among the diabetic population. RC and diabetes interacted with each other on the subsequent risk of HTN, and the desired management of RC, glucose, and cardiovascular risk factors on HTN risk was quite favorable.